Embedded copper block printed circuit board with high bonding reliability and preparation method thereof

CN122952490APending Publication Date: 2026-10-20PINGXIANG LIANJINCHENG TECH CO LTD
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
CN202611353419.4
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2026-09-02
Publication Date
2026-10-20

AI Technical Summary

Technical Problem

以上这些专利文献报道的方案主要通过PI膜或高温胶带限制压合溢胶、利用半固化片的自然流动填充铜块周边间隙,或者通过棕化微蚀和盲孔电镀改善铜块的固定及导热性能,不能同时解决铜块周边树脂充分填充、残余气体排出、机械锚固和铜与树脂界面耐湿热结合的问题

Benefits of technology

1、本发明在无氧铜块侧壁加工槽口宽度小于槽底宽度的环形锚固槽,并设置与环形锚固槽连通的导胶微槽,使压合过程中软化的环氧树脂能够进入铜块侧壁间隙并填充环形锚固槽,固化后形成倒扣式机械锚固结构,从而提高无氧铜块抵抗厚度方向推出载荷的能力。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
  • Figure SMS_2
    Figure SMS_2
  • Figure SMS_3
    Figure SMS_3
Patent Text Reader

Abstract

This invention discloses a high-reliability embedded copper block printed circuit board and its preparation method, specifically relating to the field of printed circuit board manufacturing technology. The printed circuit board comprises alternately stacked outer copper foil, prepreg, and inner core board. Internally, it has an embedded copper block receiving groove consisting of a copper block positioning section, a resin buffer section, and a resin flow channel, with an oxygen-free copper block embedded within the groove. The sidewall of the oxygen-free copper block has an annular anchoring groove and a conductive microgroove communicating with it. During preparation, the process includes inner layer circuit fabrication, receiving groove processing, copper block surface treatment, pre-lamination, staged vacuum pressing, board surface leveling, drilling electroplating, and solder resist treatment to obtain the embedded copper block printed circuit board. This invention can promote epoxy resin filling of the gaps around the copper block and the anchoring groove, improve the interfacial bonding strength between the copper block and the cured resin, and reduce interfacial debonding and cracking during damp heat aging and temperature cycling.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to the field of printed circuit board manufacturing technology, and in particular to an embedded copper block printed circuit board with high bonding reliability and its preparation method. Background Technology

[0002] As power electronic devices, high-frequency communication equipment, new energy vehicle electronic equipment, and industrial control equipment develop towards higher power density, miniaturization, and higher integration, the thermal load on printed circuit boards (PCBs) during operation is constantly increasing. Traditional PCBs mainly rely on copper foil, thermal vias, and metallized vias for heat dissipation. Their vertical thermal conductivity is limited, making it difficult to transfer the heat generated by power devices to the heat dissipation structure in a timely manner, easily causing localized overheating and affecting the operational stability and lifespan of electronic components. To improve the localized thermal conductivity and current carrying capacity of PCBs, existing technologies typically embed copper blocks within multilayer PCBs, connecting these copper blocks to power devices, outer circuitry, or heat dissipation structures to shorten the heat conduction path.

[0003] Embedded copper block printed circuit boards typically have openings machined at corresponding positions on the core board and prepreg. The copper block is then inserted into a receiving groove formed by the overlapping of these openings, and high-temperature pressing is used to allow the resin from the prepreg to flow into the gap between the copper block and the receiving groove and cure. Due to the interplay of dimensional tolerances of the copper block, machining deviations of the receiving groove, core board stacking deviations, and the flow state of the prepreg resin, problems such as copper block misalignment, insufficient perimeter filling, resin voids, localized resin overflow, and inconsistent height between the copper block surface and the board surface can easily occur during the pressing process. Especially when the gap between the copper block and the receiving groove is small, the resin may prematurely close the flow channel after entering the gap, causing residual gas to remain on the sidewalls or corners of the copper block, reducing the quality of the pressing process.

[0004] CN113891584A discloses a method for manufacturing a PCB with embedded copper blocks. This method involves placing PI films on both sides of a riveted substrate, and then sequentially placing aluminum sheets, steel plates, and kraft paper on the outside of the PI films before lamination. The PI film's conformability seals the gap between the copper block and the substrate, reducing PP adhesive overflow onto the board surface during lamination. CN110996520A discloses a method for manufacturing a double-sided circuit board with embedded copper blocks. This method involves applying high-temperature PI tape to both sides of a double-sided copper-clad laminate, milling through holes in the double-sided copper-clad laminate, inserting copper blocks, and then sequentially placing prepreg and copper foil on both sides of the double-sided copper-clad laminate before high-temperature lamination. The resin from the heated prepreg fills the gap between the copper block and the through holes, and subsequent grinding makes the surface of the copper block flush with the board surface. CN108419361A discloses a printed circuit board with embedded copper blocks and its manufacturing method. The method involves processing a receiving groove in a multi-layer bottom circuit layer, placing a heat-dissipating copper block (after browning and micro-etching) within the receiving groove, stacking a prepreg and a top circuit layer on top, and then pressing them together. Laser-drilled blind vias and through-hole plating are then used to achieve conductivity between the top circuit layer and the heat-dissipating copper block, thereby improving the heat dissipation capacity of the printed circuit board. The solutions reported in these patent documents mainly use PI film or high-temperature tape to limit adhesive overflow during pressing, utilize the natural flow of the prepreg to fill the gaps around the copper block, or improve the fixation and thermal conductivity of the copper block through browning and micro-etching and blind-hole plating. However, these solutions cannot simultaneously solve the problems of sufficient resin filling around the copper block, residual gas discharge, mechanical anchoring, and the moisture and heat resistance of the copper-resin interface. Therefore, improving the integrity of the adhesive filling around the copper block and the high-temperature, high-humidity, and temperature cycling reliability of the copper-resin interface, while ensuring the positioning accuracy and board surface flatness of the copper block, are urgent technical problems to be solved. Summary of the Invention

[0005] In view of the above-mentioned deficiencies of the prior art, the technical problem to be solved by the present invention is to provide an embedded copper block printed circuit board with high bonding reliability and its preparation method. By setting an annular anchoring groove and adhesive guiding microgroove on the sidewall of the oxygen-free copper block, and sequentially forming an AMT coordination underlayer and an organosilicon reaction layer on its surface, mechanical anchoring, copper surface coordination and epoxy co-curing are mutually coordinated, thereby improving the bonding strength and environmental reliability of the embedded copper block interface.

[0006] To achieve the above objectives, the present invention provides a method for preparing an embedded copper block printed circuit board with high bonding reliability, comprising the following steps: Step 1: Inner layer circuit fabrication and material preparation; Multiple double-sided copper-clad FR-4 core boards were selected as inner layer core boards. The inner layer core boards were sequentially subjected to film lamination, exposure, development, etching and film removal to form the inner layer circuit. After automatic optical inspection of the inner layer circuit, the copper surface of the inner layer core boards was subjected to browning treatment, water washing and drying. Prepare the first to fourth prepregs, wherein the first and fourth prepregs are high-flowability, high-glass transition temperature epoxy resin prepregs with a resin content of 56-60%, and the second and third prepregs are medium-flowability, high-glass transition temperature epoxy resin prepregs with a resin content of 46-50%. Step 2: Machining the copper block receiving groove; Openings corresponding to the installation positions of oxygen-free copper blocks are processed on each inner core board and the first to fourth semi-cured sheets, and copper block clearance windows are processed on the first and second outer copper foils. After the inner core boards are stacked, their openings together form a copper block positioning section; the openings on the first and fourth prepreg sheets extend outward by 0.2-0.3 mm on one side relative to the copper block positioning section to form a resin buffer section; the openings on the second and third prepreg sheets extend outward by 0.08-0.12 mm on one side relative to the oxygen-free copper block to form a resin flow channel; the copper block positioning section, the resin buffer section, and the resin flow channel together constitute a copper block receiving groove; Step 3: Machining and surface treatment of oxygen-free copper blocks; A continuous closed annular anchoring groove is machined on the four side walls of the oxygen-free copper block, so that the width of the groove opening is smaller than the width of the groove bottom; adhesive guiding micro-grooves extending along the thickness direction of the oxygen-free copper block are machined on each side wall of the oxygen-free copper block, so that the adhesive guiding micro-grooves are connected to the annular anchoring groove. The oxygen-free copper block is subjected to alkaline degreasing, micro-etching, water washing and drying in sequence. Then, the four sides, the annular anchoring groove and the adhesive guiding micro-groove of the oxygen-free copper block are selectively roughened. The selectively roughened oxygen-free copper block is immersed in the first treatment solution for 20-40 minutes, then rinsed with water and dried at 60-70°C for 10-15 minutes to form a coordination layer on the four sides, the annular anchoring groove, and the surface of the adhesive guiding microgroove of the oxygen-free copper block; then the second treatment solution is sprayed onto the surface of the coordination layer, and pre-baking and heating reactions are carried out in sequence. Step 4: Pre-overlay and copper block positioning; Pre-stack the materials in the following order: first outer copper foil, first prepreg, first inner core board, second prepreg, second inner core board, third prepreg, third inner core board, fourth prepreg, and second outer copper foil. By using positioning pins to align the openings on each inner core board, prepreg, and outer copper foil, the surface-treated oxygen-free copper block is inserted into the copper block positioning section, creating a one-sided gap between the four side walls of the oxygen-free copper block and the positioning section. A compressible resin compensation sheet is placed on the lower surface of the oxygen-free copper block, and polyimide release films are applied to the upper and lower surfaces of the oxygen-free copper block. Pre-pressure is applied to fix the oxygen-free copper block in the copper block receiving groove. Step 5: Staged vacuum pressing; The pre-stacked plates are placed in a vacuum press and pressed in stages under vacuum conditions; In the first stage, the pre-stacked board is heated to 85-95℃, a pressure of 0.2-0.4MPa is applied and maintained for 15-25 minutes to gradually soften the semi-cured sheet and expel the air inside the stack. In the second stage, the pre-stacked plate is heated to 130-140℃, the pressure is increased to 0.7-0.9MPa and maintained for 10-20 minutes, so that the softened epoxy resin enters the gap between the oxygen-free copper block and the copper block positioning section through the resin buffer section and the adhesive guiding micro groove, and fills the annular anchoring groove. In the third stage, the pre-stacked plates are heated to 180-190℃, the pressure is increased to 1.3-1.7MPa and maintained for 80-100min, so that the epoxy resin crosslinks and cures, and the epoxy groups in the silicone reaction layer co-cur with the epoxy resin system in the prepreg. After the pressure holding is completed, the temperature is lowered while maintaining the pressure to obtain the pressed plate. Step 6: Remove excess glue and level the board surface; Remove the polyimide release film from the upper and lower surfaces of the oxygen-free copper block. Use controlled-depth milling to remove excess adhesive from the surface and edges of the oxygen-free copper block. Then, perform double-sided grinding on the lamination plate to ensure that the exposed surface of the oxygen-free copper block is flat with the adjacent plate surface. Step 7: Drilling, electroplating, and fabrication of outer layer circuitry; Drill holes in the laminated board according to the designed hole positions, and then perform plasma degumming, chemical copper plating, and full-board electroplating in sequence; process connection holes at the locations where electrical connection with oxygen-free copper blocks is required, and use chemical copper plating and electroplating to make the copper layer on the hole wall of the connection hole electrically connected with the oxygen-free copper block; then proceed with the fabrication of the outer layer circuitry. Step 8: Solder resist and surface treatment; A solder resist layer is formed on the board surface, and solder resist openings are formed in the area of ​​the oxygen-free copper block that is used to contact the power devices. The solder resist opening area is subjected to immersion nickel gold treatment, and finally text printing, shape processing, electrical testing and finished product cleaning are performed to obtain an embedded copper block printed circuit board with high bonding reliability.

[0007] Preferably, the first treatment solution comprises 0.1-0.3 g / L of 3-amino-5-mercapto-1,2,4-triazole, 50-100 mL / L of isopropanol, and the balance being water, and the pH is adjusted to 8-8.8 using ammonia.

[0008] Preferably, the selectively roughened oxygen-free copper block is immersed in the first treatment solution for 20-40 minutes, then rinsed with water and dried at 60-70°C for 10-15 minutes.

[0009] Preferably, the second treatment solution comprises 0.2-0.6 wt% organosilicon modifier, 0.2-0.5 wt% γ-glycidyl etheroxypropyltrimethoxysilane, 0.005-0.020 wt% 2-ethyl-4-methylimidazolium, 2-4 wt% water, and the balance being a mixed solvent, wherein the mixed solvent is composed of ethanol and ethyl acetate in a mass ratio of 3:1-5:1.

[0010] The organosilicon modifier is at least one of 1,3-bis(3-aminopropyl)tetramethyldisiloxane and glycidyl POSS; preferably, the organosilicon modifier is a mixture of 1,3-bis(3-aminopropyl)tetramethyldisiloxane and glycidyl POSS in a mass ratio of (1-3):(7-9). Preferably, the second treatment liquid is sprayed onto the surface of the coordination substrate, pre-baked at 70-80°C for 10-15 minutes, and then reacted at 110-125°C for 20-30 minutes.

[0011] Preferably, when preparing the second treatment solution, γ-glycidoxypropyltrimethoxysilane, water, and ethanol in the mixed solvent are first mixed, and the pH value is adjusted to 4.3-4.7 with acetic acid. The mixture is then stirred and hydrolyzed at 20-30°C for 20-40 min. Then, an organosilicon modifier and 2-ethyl-4-methylimidazole pre-dispersed in ethyl acetate are added, and the mixture is stirred at 20-30°C for another 15-30 min to obtain the second treatment solution.

[0012] Preferably, the bottom width of the annular anchoring groove is 0.3-0.4 mm and the depth is 0.15-0.22 mm; the width of the adhesive guiding microgroove is 0.15-0.25 mm and the depth is 0.05-0.1 mm.

[0013] Preferably, a 0.04-0.08mm single-sided gap is formed between the four sides of the oxygen-free copper block and the positioning section of the copper block.

[0014] The present invention uses the above method to prepare an embedded copper block printed circuit board with high bonding reliability.

[0015] The annular anchoring groove, adhesive guiding microgroove, and roughened surface together increase the contact area between the oxygen-free copper block and the resin, forming a mechanical interlocking effect. The AMT in the first treatment solution undergoes coordination adsorption with the copper surface through thiol, amino, and nitrogen-containing heterocycles to form a coordination layer. The epoxy groups in the second treatment solution co-cur with the epoxy resin in the prepreg under the promotion of imidazole, thereby forming a composite interface between the copper block and the resin substrate that combines mechanical anchoring, coordination bonding, and chemical cross-linking.

[0016] The amino groups at both ends of 1,3-bis(3-aminopropyl)tetramethyldisiloxane can undergo a ring-opening reaction with the epoxy groups of glycidyl POSS. Its flexible disiloxane segments can alleviate the interfacial stress between the copper block and the resin caused by the difference in thermal expansion coefficients. Glycidyl POSS, on the other hand, utilizes a cage-like silicon-oxygen framework to form rigid cross-linking nodes, improving the cross-linking density, heat resistance, and dimensional stability of the interface. The synergistic effect of the two can form an interfacial structure that combines flexible segments and rigid nodes, reducing interfacial stress concentration and microcrack propagation during thermal cycling, while improving the bonding strength and damp heat resistance of the embedded copper block.

[0017] The beneficial effects of this invention are: 1. The present invention processes an annular anchoring groove with a groove opening width smaller than the groove bottom width on the side wall of the oxygen-free copper block, and sets a guide micro-groove connected to the annular anchoring groove, so that the softened epoxy resin during the pressing process can enter the gap of the side wall of the copper block and fill the annular anchoring groove. After curing, an inverted mechanical anchoring structure is formed, thereby improving the ability of the oxygen-free copper block to resist the push-out load in the thickness direction.

[0018] 2. In this invention, an AMT coordination layer is first formed on the surface of an oxygen-free copper block using a first treatment liquid, and then an organosilicon reaction layer is formed using a second treatment liquid. This creates a continuous interfacial connection structure between the surface of the oxygen-free copper block, the AMT coordination layer, the organosilicon reaction layer, and the cured epoxy resin, thereby improving the initial bonding strength between the oxygen-free copper block and the cured epoxy resin.

[0019] 3. This invention employs a combination of resin buffer section, resin flow channel and staged vacuum pressing, which allows epoxy resin to fully enter the gaps around the oxygen-free copper block, the adhesive guiding microgroove and the annular anchoring groove before gel curing, and to expel air from the stack, thereby reducing missing adhesive and voids around the copper block, improving the pressing quality and long-term reliability of the embedded copper block printed circuit board. Detailed Implementation

[0020] The endpoints and any values ​​of the ranges disclosed in this invention are not limited to the precise ranges or values, and these ranges or values ​​should be understood to include values ​​close to these ranges or values. For numerical ranges, the endpoint values ​​of the various ranges, the endpoint values ​​of the various ranges and individual point values, and individual point values ​​can be combined with each other to obtain one or more new numerical ranges, which should be considered as specifically disclosed in this invention.

[0021] The first to fourth prepregs are all S1000-2M series high glass transition temperature epoxy resin prepregs manufactured by Guangdong Shengyi Technology Co., Ltd. These prepregs use a high Tg epoxy resin system, and their glass transition temperature after curing is 170℃. Specifically, the first and fourth prepregs are high-flowability prepregs (model S1000-2M / 2116) with a resin content of 58±2%; the second and third prepregs are medium-flowability prepregs (model S1000-2M / 7628) with a resin content of 48±2%. All of the above prepregs are manufactured by Guangdong Shengyi Technology Co., Ltd.

[0022] A 0.05 mm thick polyimide release film is applied to both the upper and lower surfaces of the oxygen-free copper block. The polyimide release film is a Kapton membrane manufactured by DuPont. ® 200HN type polyimide film.

[0023] Glycidyl-based POSS uses EP0409 type Glycidyl POSS manufactured by Hybrid Plastics, Inc., USA. ® Cage Mixture; The octaisobutyl POSS used is MS0825 type OctaIsobutyl POSS manufactured by Hybrid Plastics, Inc., USA. Other raw materials not mentioned are all common raw materials. The above content is only for the purpose of illustrating the present invention and should not be construed as a strict limitation of the present invention. Those skilled in the art can directly purchase the same / similar raw materials from the market or prepare them themselves.

[0024] The technical solutions of the present invention will be clearly and completely described below with reference to specific embodiments. Obviously, the described embodiments are only some embodiments of the present invention, and not all embodiments. Based on the embodiments of the present invention, all other embodiments obtained by those skilled in the art without creative effort are within the scope of protection of the present invention.

[0025] Example 1 A method for preparing an embedded copper block printed circuit board with high bonding reliability, wherein the prepared embedded copper block printed circuit board is an eight-layer printed circuit board with a finished board thickness of 2.4 mm, comprising a first outer copper foil, a first prepreg, a first inner core board, a second prepreg, a second inner core board, a third prepreg, a third inner core board, a fourth prepreg, and a second outer copper foil stacked sequentially; a copper block receiving groove is formed inside the printed circuit board, and an oxygen-free copper block is embedded in the copper block receiving groove. The specific preparation method includes the following steps: Step 1: Inner layer circuit fabrication and material preparation; Three double-sided copper-clad FR-4 core boards, each with a thickness of 0.4 mm, were selected as the first, second, and third inner layer core boards, respectively. The glass transition temperature of the FR-4 core boards is 170℃. The inner layer circuitry was formed by sequentially applying film, exposing, developing, etching, and removing the film according to the design pattern. The inner layer circuitry was then subjected to automatic optical inspection to confirm that there were no open circuits, short circuits, gaps, or residual copper. After that, the copper surface of the core boards was browned, washed with water, and dried at 100℃ for 30 min. The first to fourth prepregs are all high glass transition temperature epoxy resin prepregs; the first prepreg near the upper surface of the oxygen-free copper block and the fourth prepreg near the lower surface of the oxygen-free copper block are high flow prepregs with a resin content of 58%, while the second and third prepregs are medium flow prepregs with a resin content of 48%. Step 2: Machining the copper block receiving groove; Openings corresponding to the installation positions of the oxygen-free copper blocks are machined on the first inner core board, the second inner core board, the third inner core board, and the first to fourth prepreg sheets. Copper block clearance windows are machined on the first and second outer copper foils. The inner core boards are machined using CNC milling. A 0.08mm finishing allowance is reserved during rough machining. Then, a 1mm diameter double-edged milling cutter is used for finishing. The finishing feed rate is 0.8m / min, and the spindle speed is 36000r / min. After the inner core boards are stacked, their openings together form the copper block positioning section. The openings on the first and fourth prepregs extend outward by 0.25 mm on one side relative to the copper block positioning section to form resin buffer sections located on the upper and lower sides of the copper block positioning section; the openings on the second and third prepregs extend outward by 0.1 mm on one side relative to the oxygen-free copper block to form resin flow channels. The position and size of each opening are detected by a three-dimensional optical measurement device, so that the center position deviation of the opening of the adjacent inner core board does not exceed 0.05mm, the verticality deviation of the groove wall of the copper block positioning section does not exceed 0.08mm, and the cumulative height deviation of the overlapping area does not exceed 0.05mm. The copper block positioning section, the resin buffer section and the resin flow channel together constitute the copper block receiving groove. Step 3: Machining and surface treatment of oxygen-free copper blocks; The oxygen-free copper plate is processed into an oxygen-free copper block with a length of 16mm, a width of 12mm, and a thickness of 2.35mm; a continuous closed annular anchoring groove is set on the four sides of the oxygen-free copper block. The bottom width of the annular anchoring groove is 0.35mm and the depth is 0.18mm, and the width of the groove opening is smaller than the bottom width. Each sidewall of the oxygen-free copper block is also provided with two adhesive guiding microgrooves extending along the thickness direction. The adhesive guiding microgrooves are connected to the annular anchoring groove, with a width of 0.2 mm and a depth of 0.08 mm. The edges of the oxygen-free copper block are rounded with a rounding radius of 0.1 mm. The processed oxygen-free copper block was subjected to alkaline degreasing, micro-etching, water washing, and drying in sequence, with the micro-etching depth controlled at 2μm. The four sides, annular anchoring groove, and adhesive guiding micro-groove of the oxygen-free copper block were selectively roughened to achieve a surface roughness Ra of 2.2μm. After selective roughening, the oxygen-free copper block was thoroughly washed with water and dried at 60℃ for 10min. Subsequently, the oxygen-free copper block was immersed in the treatment solution for 30min, removed, and quickly rinsed with water for 5s, followed by drying at 65℃ for 12min. The treatment solution comprises 1% by mass of γ-glycidoxypropyltrimethoxysilane, 4% by mass of water, and the balance being ethanol, and its pH is adjusted to 4.5 using acetic acid. Step 4: Pre-overlay and copper block positioning; Pre-stack the materials in the following order: first outer copper foil, first prepreg, first inner core board, second prepreg, second inner core board, third prepreg, third inner core board, fourth prepreg, and second outer copper foil. During pre-assembly, the openings on each inner core board, prepreg, and outer copper foil are aligned coaxially using positioning pins, and then the oxygen-free copper block is installed into the copper block positioning section; a 0.05mm single-sided gap is formed between the four sides of the oxygen-free copper block and the copper block positioning section. A compressible resin compensation sheet with a thickness of 0.05mm is set on the lower surface of the oxygen-free copper block, and the height of the oxygen-free copper block relative to the reference surface of the pre-stacked plate is detected by a four-point height measurement method, so that the upper surface of the oxygen-free copper block is 0.045mm higher than the reference surface of the pre-stacked plate. A 0.05mm thick polyimide release film is applied to the upper and lower surfaces of the oxygen-free copper block. The outer perimeter of the polyimide release film is 0.15mm smaller on one side than the corresponding surface of the oxygen-free copper block, which isolates the central area of ​​the oxygen-free copper block from the pressing template, while allowing the edge area of ​​the oxygen-free copper block to withstand the pressing pressure. After pre-overlapping, the oxygen-free copper block is held under a pre-pressure of 0.15MPa for 60s to initially fix the oxygen-free copper block and control the planar deviation of the oxygen-free copper block relative to the design position to within 0.08mm. Step 5: Staged vacuum pressing; The pre-stacked plates are placed in a vacuum press and pressed in stages under a vacuum of 5 kPa. In the first stage, the temperature is increased from room temperature to 90°C at a heating rate of 2°C / min, and a pressure of 0.3MPa is applied and maintained for 20min to gradually soften the semi-cured sheet and expel the air inside the stack. In the second stage, the temperature is increased to 135℃ at a heating rate of 1.5℃ / min, the pressure is increased to 0.8MPa and held for 15min, so that the softened epoxy resin enters the gap between the oxygen-free copper block and the copper block positioning section through the resin buffer section and the adhesive guiding micro-groove, and fills the annular anchoring groove. In the third stage, the temperature is increased to 185°C at a heating rate of 1°C / min, the pressure is increased to 1.5MPa and held for 90 minutes to allow the epoxy resin to crosslink and cure. After the pressure holding is completed, the temperature is cooled to 100°C at a cooling rate of 2°C / min while maintaining a pressure of 1.5MPa. Then the pressure is released and the temperature is further cooled to 45°C to obtain the pressed board. Step 6: Remove excess glue and level the board surface; Remove the polyimide release film from the upper and lower surfaces of the oxygen-free copper block. Use CNC deep milling to remove excess adhesive from the surface and edges of the oxygen-free copper block, with a milling allowance of 0.03mm. Then, use 600-mesh and 1000-mesh ceramic brush rollers to perform double-sided grinding on the pressed plate, so that the height difference between the exposed surface of the oxygen-free copper block and the adjacent plate surface is within ±0.03mm. During the grinding process, first grind 0.03mm on the first surface of the press plate, then flip the press plate over and grind the same thickness on the second surface. Repeat the above double-sided grinding operation twice. After grinding, remove the residual resin and copper shavings from the plate surface and check the thickness and warpage of the press plate. Step 7: Drilling, electroplating, and fabrication of outer layer circuitry; The press plate was CNC drilled according to the designed hole positions, and then plasma degumming, chemical copper plating, and full-board electroplating were performed in sequence; the chemical copper plating layer thickness was 0.65μm, and the average thickness of the copper layer on the hole wall after full-board electroplating was 25μm. Connecting holes are machined at the locations where electrical connection with the oxygen-free copper block is required, extending the connecting holes to the oxygen-free copper block; after plasma descaling, chemical copper plating and electroplating, the copper layer on the hole wall forms an electrical connection with the oxygen-free copper block. Then, according to the design pattern, the outer layer is applied, exposed, developed, patterned electroplated, stripped and etched to form the outer layer circuit. Step 8: Solder resist and surface treatment; Solder resist ink is printed on the board surface, and solder resist openings are formed in the area of ​​the oxygen-free copper block that is used to contact the power devices; the solder resist opening area is subjected to immersion nickel-gold treatment, wherein the nickel layer thickness is 4μm and the gold layer thickness is 0.075μm. Finally, text printing, shape processing, electrical testing, and finished product cleaning are carried out to obtain an embedded copper block printed circuit board with high integration reliability.

[0026] Example 2 A method for preparing an embedded copper block printed circuit board with high bonding reliability, wherein the prepared embedded copper block printed circuit board is an eight-layer printed circuit board with a finished board thickness of 2.4 mm, comprising a first outer copper foil, a first prepreg, a first inner core board, a second prepreg, a second inner core board, a third prepreg, a third inner core board, a fourth prepreg, and a second outer copper foil stacked sequentially; a copper block receiving groove is formed inside the printed circuit board, and an oxygen-free copper block is embedded in the copper block receiving groove. The specific preparation method includes the following steps: Step 1: Inner layer circuit fabrication and material preparation; Three double-sided copper-clad FR-4 core boards, each with a thickness of 0.4 mm, were selected as the first, second, and third inner layer core boards, respectively. The glass transition temperature of the FR-4 core boards is 170℃. The inner layer circuitry was formed by sequentially applying film, exposing, developing, etching, and removing the film according to the design pattern. The inner layer circuitry was then subjected to automatic optical inspection to confirm that there were no open circuits, short circuits, gaps, or residual copper. After that, the copper surface of the core boards was browned, washed with water, and dried at 100℃ for 30 min. The first to fourth prepregs are all high glass transition temperature epoxy resin prepregs; the first prepreg near the upper surface of the oxygen-free copper block and the fourth prepreg near the lower surface of the oxygen-free copper block are high flow prepregs with a resin content of 58%, while the second and third prepregs are medium flow prepregs with a resin content of 48%. Step 2: Machining the copper block receiving groove; Openings corresponding to the installation positions of the oxygen-free copper blocks are machined on the first inner core board, the second inner core board, the third inner core board, and the first to fourth prepreg sheets. Copper block clearance windows are machined on the first and second outer copper foils. The inner core boards are machined using CNC milling. A 0.08mm finishing allowance is reserved during rough machining. Then, a 1mm diameter double-edged milling cutter is used for finishing. The finishing feed rate is 0.8m / min, and the spindle speed is 36000r / min. After the inner core boards are stacked, their openings together form the copper block positioning section. The openings on the first and fourth prepregs extend outward by 0.25 mm on one side relative to the copper block positioning section to form resin buffer sections located on the upper and lower sides of the copper block positioning section; the openings on the second and third prepregs extend outward by 0.1 mm on one side relative to the oxygen-free copper block to form resin flow channels. The position and size of each opening are detected by a three-dimensional optical measurement device, so that the center position deviation of the opening of the adjacent inner core board does not exceed 0.05mm, the verticality deviation of the groove wall of the copper block positioning section does not exceed 0.08mm, and the cumulative height deviation of the overlapping area does not exceed 0.05mm. The copper block positioning section, the resin buffer section and the resin flow channel together constitute the copper block receiving groove. Step 3: Machining and surface treatment of oxygen-free copper blocks; The oxygen-free copper plate is processed into an oxygen-free copper block with a length of 16mm, a width of 12mm, and a thickness of 2.35mm. A continuous closed annular anchoring groove is set on the four sides of the oxygen-free copper block. The bottom width of the annular anchoring groove is 0.35mm and the depth is 0.18mm. The width of the groove opening is smaller than the bottom width. Each sidewall of the oxygen-free copper block is also provided with two adhesive guiding microgrooves extending along the thickness direction. The adhesive guiding microgrooves are connected to the annular anchoring groove, with a width of 0.2 mm and a depth of 0.08 mm. The edges of the oxygen-free copper block are rounded with a rounding radius of 0.1 mm. The processed oxygen-free copper block was subjected to alkaline degreasing, micro-etching, water washing, and drying in sequence, with the micro-etching depth controlled at 2 μm. The four sides, annular anchoring groove, and adhesive guiding micro-groove of the oxygen-free copper block were selectively roughened to achieve a surface roughness Ra of 2.2 μm. After selective roughening, the oxygen-free copper block was thoroughly washed with water and dried at 60°C for 10 min. Subsequently, the oxygen-free copper block was immersed in the first treatment solution for 30 min, removed, and quickly rinsed with water for 5 s, followed by drying at 65°C for 12 min. The first treatment solution comprises 0.2 g / L 3-amino-5-mercapto-1,2,4-triazole (CAS: 16691-43-3), 75 mL / L isopropanol, and the balance being water, with the pH adjusted to 8.4 using 25% ammonia solution. The second treatment liquid was sprayed onto the surface of the coordination substrate treated with the first treatment liquid. During the coating process, the upper and lower surfaces of the oxygen-free copper block were kept in a protected state to prevent the POSS reaction liquid from covering the areas to be used for thermal contact and electrical connection. After coating, the surface was pre-baked at 75°C for 12 min, and then reacted at 120°C for 25 min. After the reaction was completed and cooled to room temperature, the acid and alkali resistant protective film covering the upper and lower surfaces of the oxygen-free copper block was removed. The protected area was wiped with a lint-free cloth soaked in isopropanol and dried at 70°C for 10 min. The second treatment solution comprises 0.45 wt% glycidyl POSS, 0.35 wt% γ-glycidyl etheroxypropyltrimethoxysilane (CAS: 2530-83-8), 0.01 wt% 2-ethyl-4-methylimidazole (CAS: 931-36-2), 3 wt% water, and the balance being a mixed solvent, wherein the mixed solvent is a mixture of ethanol and ethyl acetate in a mass ratio of 4:1. To prepare the second treatment solution, γ-glycidoxypropyltrimethoxysilane, water, and ethanol in the mixed solvent are first mixed, and the pH value is adjusted to 4.5 using acetic acid. The mixture is then stirred and hydrolyzed at 25°C for 30 min. Next, glycidyl POSS and 2-ethyl-4-methylimidazole are dispersed in ethyl acetate, and the hydrolyzed mixture is added. The mixture is stirred at 25°C for another 20 min to obtain the second treatment solution. Step 4: Pre-overlay and copper block positioning; Pre-stack the materials in the following order: first outer copper foil, first prepreg, first inner core board, second prepreg, second inner core board, third prepreg, third inner core board, fourth prepreg, and second outer copper foil. During pre-assembly, the openings on each inner core board, prepreg, and outer copper foil are aligned coaxially using positioning pins, and then the oxygen-free copper block is installed into the copper block positioning section; a 0.05mm single-sided gap is formed between the four sides of the oxygen-free copper block and the copper block positioning section. A compressible resin compensation sheet with a thickness of 0.05mm is set on the lower surface of the oxygen-free copper block, and the height of the oxygen-free copper block relative to the reference surface of the pre-stacked plate is detected by a four-point height measurement method, so that the upper surface of the oxygen-free copper block is 0.045mm higher than the reference surface of the pre-stacked plate. A 0.05mm thick polyimide release film is applied to the upper and lower surfaces of the oxygen-free copper block. The outer perimeter of the polyimide release film is 0.15mm smaller on one side than the corresponding surface of the oxygen-free copper block, which isolates the central area of ​​the oxygen-free copper block from the pressing template, while allowing the edge area of ​​the oxygen-free copper block to withstand the pressing pressure. After pre-overlapping, the oxygen-free copper block is held under a pre-pressure of 0.15MPa for 60s to initially fix the oxygen-free copper block and control the planar deviation of the oxygen-free copper block relative to the design position to within 0.08mm. Step 5: Staged vacuum pressing; The pre-stacked plates are placed in a vacuum press and pressed in stages under a vacuum of 5 kPa. In the first stage, the temperature is increased from room temperature to 90°C at a heating rate of 2°C / min, and a pressure of 0.3MPa is applied and maintained for 20min to gradually soften the semi-cured sheet and expel the air inside the stack. In the second stage, the temperature is increased to 135℃ at a heating rate of 1.5℃ / min, the pressure is increased to 0.8MPa and held for 15min, so that the softened epoxy resin enters the gap between the oxygen-free copper block and the copper block positioning section through the resin buffer section and the adhesive guiding micro-groove, and fills the annular anchoring groove. In the third stage, the temperature is increased to 185°C at a heating rate of 1°C / min, the pressure is increased to 1.5MPa and held for 90 minutes to allow the epoxy resin to crosslink and cure. After the pressure holding is completed, the temperature is cooled to 100°C at a cooling rate of 2°C / min while maintaining a pressure of 1.5MPa. Then the pressure is released and the temperature is further cooled to 45°C to obtain the pressed board. Step 6: Remove excess glue and level the board surface; Remove the polyimide release film from the upper and lower surfaces of the oxygen-free copper block. Use CNC deep milling to remove excess adhesive from the surface and edges of the oxygen-free copper block, with a milling allowance of 0.03mm. Then, use 600-mesh and 1000-mesh ceramic brush rollers to perform double-sided grinding on the pressed plate, so that the height difference between the exposed surface of the oxygen-free copper block and the adjacent plate surface is within ±0.03mm. During the grinding process, first grind 0.03mm on the first surface of the press plate, then flip the press plate over and grind the same thickness on the second surface. Repeat the above double-sided grinding operation twice. After grinding, remove the residual resin and copper shavings from the plate surface and check the thickness and warpage of the press plate. Step 7: Drilling, electroplating, and fabrication of outer layer circuitry; The press plate was CNC drilled according to the designed hole positions, and then plasma degumming, chemical copper plating, and full-board electroplating were performed in sequence; the chemical copper plating layer thickness was 0.65μm, and the average thickness of the copper layer on the hole wall after full-board electroplating was 25μm. Connecting holes are machined at the locations where electrical connection with the oxygen-free copper block is required, extending the connecting holes to the oxygen-free copper block; after plasma descaling, chemical copper plating and electroplating, the copper layer on the hole wall forms an electrical connection with the oxygen-free copper block. Then, according to the design pattern, the outer layer is applied, exposed, developed, patterned electroplated, stripped and etched to form the outer layer circuit. Step 8: Solder resist and surface treatment; Solder resist ink is printed on the board surface, and solder resist openings are formed in the area of ​​the oxygen-free copper block that is used to contact the power devices; the solder resist opening area is subjected to immersion nickel-gold treatment, wherein the nickel layer thickness is 4μm and the gold layer thickness is 0.075μm. Finally, text printing, shape processing, electrical testing, and finished product cleaning are carried out to obtain an embedded copper block printed circuit board with high integration reliability.

[0027] Example 3 The process is basically the same as in Example 2, except that after selective roughening, the oxygen-free copper block is treated with only the first treatment solution to form the AMT coordination layer, and no second treatment solution is used.

[0028] The oxygen-free copper block was processed, degreased, micro-etched, and selectively roughened according to the method in step 3 of Example 2, so that the surface roughness Ra of its four side walls, annular anchor groove, and adhesive guiding microgroove was 2.2 μm.

[0029] The oxygen-free copper block was immersed in the first treatment solution for 30 minutes, then rinsed quickly with water for 5 seconds and dried at 65°C for 12 minutes to form the AMT coordination substrate. The first treatment solution consisted of 0.2 g / L of 3-amino-5-mercapto-1,2,4-triazole, 75 mL / L of isopropanol, and the balance being water, with the pH adjusted to 8.4 using 25% ammonia solution.

[0030] Subsequently, without using the second processing solution, the process is carried out directly according to steps 4 to 8 of Example 2 to obtain the embedded copper block printed circuit board.

[0031] Example 4 The process is basically the same as in Example 2, except that after selective roughening, the oxygen-free copper block is not treated with the first treatment solution to form the AMT coordination layer, but is directly treated with the second treatment solution.

[0032] The oxygen-free copper block was processed, degreased, micro-etched, and selectively roughened according to step 3 of Example 2, so that the surface roughness Ra of its four sidewalls, annular anchor groove, and adhesive guiding microgroove was 2.2 μm. After cleaning and drying, an acid and alkali resistant protective film was applied to cover the upper and lower surfaces of the oxygen-free copper block, and then the second treatment solution was sprayed onto its four sidewalls, annular anchor groove, and adhesive guiding microgroove.

[0033] The second treatment solution comprises 0.4 wt% glycidyl POSS, 0.35 wt% γ-glycidyl etheroxypropyltrimethoxysilane, 0.01 wt% 2-ethyl-4-methylimidazole, 3 wt% water, and the balance being a mixed solvent, wherein the mixed solvent is a mixture of ethanol and ethyl acetate in a mass ratio of 4:1.

[0034] After spraying, pre-bake at 75°C for 12 minutes, then react at 120°C for 25 minutes. After the reaction, remove the acid and alkali resistant protective film, and process according to steps 4 to 8 of Example 2 to obtain the embedded copper block printed circuit board.

[0035] Example 5 It is basically the same as Example 2, except that after forming the AMT coordination layer, a second treatment solution without glycidyl group POSS is used for treatment.

[0036] Specifically, the oxygen-free copper block is processed, degreased, micro-etched, selectively roughened, and immersed in the first treatment solution according to the method described in step 3 of Example 2, and an AMT coordination underlayer is formed on the four side walls, the annular anchoring groove, and the adhesive guiding microgroove of the oxygen-free copper block.

[0037] The control treatment solution was then sprayed onto the surface of the AMT coordination substrate using a spraying method. The control treatment solution comprised 0.35 wt% γ-glycidyl etheroxypropyltrimethoxysilane, 0.01 wt% 2-ethyl-4-methylimidazole, 3% water, and the balance being a mixed solvent composed of ethanol and ethyl acetate in a 4:1 mass ratio.

[0038] In preparation, γ-glycidoxypropyltrimethoxysilane, water and ethanol were first mixed, and the pH was adjusted to 4.5 with acetic acid. The mixture was then stirred and hydrolyzed at 25°C for 30 min. 2-Ethyl-4-methylimidazole and ethyl acetate were then added, and the mixture was stirred at 25°C for another 20 min to obtain the control treatment solution.

[0039] After spraying the control treatment solution onto the surface of the AMT coordination substrate, pre-baking was carried out at 75°C for 12 min, followed by reaction at 120°C for 25 min. After the reaction was completed and cooled to room temperature, the acid and alkali resistant protective film covering the upper and lower surfaces of the oxygen-free copper block was removed. The protected area was wiped with a lint-free cloth soaked in isopropanol and dried at 70°C for 10 min.

[0040] The process is then carried out according to steps 4 to 8 of Example 2 to obtain the embedded copper block printed circuit board.

[0041] Example 6 This is basically the same as Example 2, except that the oxygen-free copper block is not treated with the first and second treatment solutions after selective roughening.

[0042] Specifically, the oxygen-free copper block was processed, alkaline degreasing, micro-etching, water washing, drying, and selective roughening were performed according to the method described in step 3 of Example 2, so that the surface roughness Ra of the four sidewalls, annular anchoring groove, and adhesive guiding microgroove of the oxygen-free copper block was 2.2 μm. After selective roughening, the oxygen-free copper block was thoroughly washed with water and dried at 70°C for 10 min.

[0043] Instead of using the first and second treatment solutions to process the oxygen-free copper blocks, the process is directly carried out according to steps 4 to 8 of Example 2, including pre-overlay, copper block positioning, staged vacuum pressing, excess adhesive removal, board surface leveling, drilling, electroplating, outer layer circuit fabrication, solder masking, and surface treatment, to obtain an embedded copper block printed circuit board.

[0044] Example 7 It is basically the same as Example 2, except that 2-ethyl-4-methylimidazole is not added to the second treatment solution.

[0045] Specifically, the oxygen-free copper block is processed, alkaline degreasing, micro-etching, water washing, drying and selective roughening are performed according to the method described in step 3 of Example 2, and then immersed in the first treatment solution to form an AMT coordination underlayer on the four side walls, the annular anchoring groove and the adhesive guiding micro groove of the oxygen-free copper block.

[0046] The second treatment solution is sprayed onto the surface of the AMT coordination substrate by a spraying method. The second treatment solution includes 0.45% glycidyl POSS by mass, 0.35% γ-glycidyl etheroxypropyltrimethoxysilane by mass, 3% water by mass, and the balance being a mixed solvent composed of ethanol and ethyl acetate in a mass ratio of 4:1.

[0047] After coating, the substrate was pre-baked at 75°C for 12 minutes, followed by reaction at 120°C for 25 minutes. Then, it was processed according to steps 4 to 8 of Example 2 to obtain an embedded copper block printed circuit board.

[0048] Example 8 It is basically the same as Example 2, except that: octaisobutyl POSS without reactive glycidyl groups is used to replace glycidyl POSS by mass.

[0049] Specifically, an AMT coordination underlayer is formed on the four sides of the oxygen-free copper block, the annular anchoring groove, and the surface of the adhesive guiding microgroove, according to the method described in step 3 of Example 2.

[0050] The second treatment solution was then sprayed onto the surface of the AMT coordination substrate using a spraying method. The second treatment solution included: 0.45% by mass of octaisobutylPOSS, 0.35% by mass of γ-glycidyl etheroxypropyltrimethoxysilane, 0.01% by mass of 2-ethyl-4-methylimidazole, 3% by mass of water, and the balance being a mixed solvent composed of ethanol and ethyl acetate in a mass ratio of 4:1.

[0051] After coating, pre-bake at 75°C for 12 minutes, then process at 120°C for 25 minutes. Afterwards, process according to steps 4 to 8 of Example 2 to obtain the embedded copper block printed circuit board.

[0052] Example 9 The process is basically the same as in Example 2, except that the AMT and POSS components are mixed into a treatment solution and treated with a single spraying method, without forming the AMT coordination underlayer and the glycidyl-based POSS reaction layer separately.

[0053] Specifically, the oxygen-free copper block is processed and subjected to alkaline degreasing, micro-etching, water washing, drying and selective roughening, so that the surface roughness Ra of its four side walls, annular anchoring groove and adhesive guiding micro-groove is 2.2μm.

[0054] A mixed treatment solution is prepared, comprising 0.02 wt% 3-amino-5-mercapto-1,2,4-triazole, 0.45 wt% glycidyl POSS, 0.35 wt% γ-glycidyl etheroxypropyltrimethoxysilane, 0.01 wt% 2-ethyl-4-methylimidazole, 3 wt% water, and the balance being a mixed solvent, wherein the mixed solvent is prepared by mixing ethanol and ethyl acetate in a mass ratio of 4:1.

[0055] The mixed treatment solution was uniformly sprayed onto the four sides of the oxygen-free copper block, the annular anchor groove, and the surface of the adhesive guiding microgroove. It was pre-baked at 75°C for 12 minutes, followed by a reaction at 120°C for 25 minutes. Then, it was processed according to steps 4 to 8 of Example 2 to obtain the embedded copper block printed circuit board.

[0056] Example 10 The process is basically the same as in Example 2, except that: a glycidyl-based POSS layer is first formed on the surface of the oxygen-free copper block, and then AMT treatment is performed using the first treatment solution. That is, the interface treatment sequence is the reverse of that in Example 2.

[0057] Specifically, the selectively roughened oxygen-free copper block was sprayed with a second treatment solution, the composition of which was the same as in Example 2. After spraying, it was pre-baked at 75°C for 12 minutes, without undergoing a reaction treatment at 120°C. The oxygen-free copper block coated with the second treatment solution was then immersed in the first treatment solution and treated at 42°C for 30 minutes. The first treatment solution consisted of 0.2 g / L of 3-amino-5-mercapto-1,2,4-triazole, 75 mL / L of isopropanol, and the remainder was water, with the pH adjusted to 8.4 using 25% ammonia solution. After processing, the substrate is quickly rinsed with water for 5 seconds, dried at 65°C for 12 minutes, and then reacted at 120°C for 25 minutes. Subsequently, it is processed according to steps 4 to 8 of Example 2 to obtain an embedded copper block printed circuit board.

[0058] Example 11 It is basically the same as Example 2, except that the second treatment solution does not contain γ-glycidoxypropyltrimethoxysilane.

[0059] The second treatment solution comprises 0.45 wt% glycidyl POSS, 0.01 wt% 2-ethyl-4-methylimidazole, 3 wt% water, and the balance being a mixed solvent, wherein the mixed solvent is composed of ethanol and ethyl acetate mixed in a mass ratio of 4:1.

[0060] The second treatment solution was sprayed onto the surface of the AMT coordination substrate and pre-baked at 75°C for 12 min, followed by reaction at 120°C for 25 min. Then, it was processed according to steps 4 to 8 of Example 2 to obtain an embedded copper block printed circuit board.

[0061] Example 12 It is basically the same as Example 2, except that the second treatment solution is different; The second treatment solution comprises 0.4 wt% glycidyl POSS, 0.35 wt% γ-glycidyl etheroxypropyltrimethoxysilane, 0.05 wt% 1,3-bis(3-aminopropyl)tetramethyldisiloxane (CAS: 2469-55-8), 0.01 wt% 2-ethyl-4-methylimidazolium, 3 wt% water, and the balance being a mixed solvent, wherein the mixed solvent is prepared by mixing ethanol and ethyl acetate in a mass ratio of 4:1.

[0062] In preparing the second treatment solution, γ-glycidyl etheroxypropyltrimethoxysilane, water, and ethanol in the mixed solvent were first mixed, and the pH was adjusted to 4.5 with acetic acid. The mixture was then stirred and hydrolyzed at 25°C for 30 min. Glycidyl POSS and 2-ethyl-4-methylimidazole were dispersed in ethyl acetate, and then 1,3-bis(3-aminopropyl)tetramethyldisiloxane was added. The mixture was stirred at 25°C for 10 min to obtain an organic dispersion. This organic dispersion was added to the hydrolyzed mixture, and the mixture was stirred at 25°C for another 20 min to obtain the second treatment solution. The second treatment solution was sprayed onto the surface of the AMT coordination substrate, allowed to stand and level for 5 min, pre-baked at 75°C for 12 min, and then reacted at 120°C for 25 min. After the reaction was completed, the mixture was processed according to steps 4 to 8 of Example 2 to obtain an embedded copper block printed circuit board.

[0063] Example 13 It is basically the same as Example 12, except that glycidyl-based POSS is not added to the second treatment solution.

[0064] The oxygen-free copper block is processed, degreased, micro-etched, selectively roughened, and immersed in the first treatment solution according to the method of step 3 in Example 2, so that AMT coordination underlayer is formed on its surrounding sidewalls, annular anchoring groove, and adhesive guiding microgroove surface.

[0065] To prepare the second treatment solution, 0.35 wt% of γ-glycidoxypropyltrimethoxysilane, 3 wt% of water, and ethanol from the mixed solvent were mixed. The pH was adjusted to 4.5 using acetic acid, and the mixture was stirred and hydrolyzed at 25°C for 30 min. Then, 0.45 wt% of 1,3-bis(3-aminopropyl)tetramethyldisiloxane and 0.01 wt% of 2-ethyl-4-methylimidazolium were dispersed in ethyl acetate, and the hydrolyzed mixture was added. The mixture was stirred at 25°C for another 20 min to obtain the second treatment solution. The mixed solvent was prepared by mixing ethanol and ethyl acetate in a mass ratio of 4:1.

[0066] The second treatment solution was sprayed onto the surface of the AMT coordination substrate, allowed to stand and level for 5 minutes, pre-baked at 75°C for 12 minutes, and then reacted at 120°C for 25 minutes. After the reaction was completed, it was processed according to steps 4 to 8 of Example 2 to obtain the embedded copper block printed circuit board.

[0067] Test Example 1 Ten parallel samples were prepared in each group using the embedded copper block printed circuit boards prepared in the examples. Each sample was placed in an environment with a temperature of 23±2℃ and a relative humidity of 50±5% for 24 hours to adjust.

[0068] The sample is horizontally fixed on the support fixture of the universal testing machine. The support fixture has a rectangular clearance hole with a length of 17mm and a width of 13mm in the center. The clearance hole is coaxial with the oxygen-free copper block, so that the printed circuit board body is supported, and the oxygen-free copper block can move along the thickness direction of the printed circuit board.

[0069] A force sensor with a range of 5 kN and an accuracy of 0.5 grade, along with a rectangular indenter 14 mm long and 10 mm wide with a flat loading end face, was used to uniformly apply a load from one exposed surface of the oxygen-free copper block to the opposite exposed surface at a loading speed of 0.5 mm / min. When interfacial disruption and continuous displacement occurred between the oxygen-free copper block and the surrounding cured epoxy resin, the corresponding maximum load was recorded and used as the initial pushing force of the copper block. The average value of 10 samples was taken for each set of results, and the standard deviation was calculated.

[0070] The nominal equivalent shear strength of the copper block interface is calculated according to the following formula:

[0071] In the formula, τ0 is the nominal equivalent shear strength of the copper block interface, in MPa; F0 is the initial pushing force of the copper block, in N; L is the length of the oxygen-free copper block, taken as 16mm; W is the width of the oxygen-free copper block, taken as 12mm; and H is the thickness of the oxygen-free copper block, taken as 2.35mm.

[0072] Table 1 Test results of initial ejection force of printed circuit board with embedded copper block

[0073] As shown in Table 1, the initial push-out force of Example 12 was 2294 N, the highest among all groups, and 3.5% higher than that of Example 2. The initial push-out force of Example 13 was 1986 N, lower than that of Example 12, but 7.4% higher than that of Example 5, which did not contain glycidyl POSS and disiloxane bridging components. The above results indicate that 1,3-bis(3-aminopropyl)tetramethyldisiloxane can improve the continuity of the interfacial reaction layer, and that glycidyl POSS and disiloxane bridging structures have higher initial bonding strength when they coexist.

[0074] Example 7 did not include 2-ethyl-4-methylimidazole, resulting in a reduced degree of interfacial ring-opening reaction; Example 8 used non-reactive octaisobutyl POSS instead of glycidyl POSS, preventing its participation in epoxy co-curing; Example 9 employed a single-stage mixing process, preventing AMT from preferentially forming a continuous coordination layer on the copper surface; Example 10 used the reverse processing sequence, causing the POSS layer to mask some coordination sites on the copper surface; Example 11 lacked epoxy silanes, reducing the wetting and film continuity of the treated layer. Therefore, the initial ejection force of all the above groups was lower than that of Example 2.

[0075] Example 12 contains both glycidyl POSS and 1,3-bis(3-aminopropyl)tetramethyldisiloxane, which can form a POSS cage-like node and a disiloxane bridging structure; Example 13 does not contain glycidyl POSS and lacks rigid silicon-oxygen cage-like nodes, so its initial push-out force is lower than that of Example 12.

[0076] Test Example 2 Ten independent samples were selected from each of the examples and placed in a constant temperature and humidity test chamber at 85±2℃ and 85±3% for 1000h.

[0077] After the treatment, the sample was removed, the condensate on its surface was wiped off, and it was placed in an environment with a temperature of 23±2℃ and a relative humidity of 50±5% for 2 hours. Then, the pushing force of the copper block after high temperature and high humidity aging was measured according to the method described in Test Example 1.

[0078] The extrusion force retention rate after high temperature and high humidity aging is calculated according to the following formula: R h =F h / F0×100% In the formula, R h F represents the rate of retention of extrusion force after high temperature and high humidity aging. h F0 represents the average pushing force after high temperature and high humidity aging, in N; F0 represents the initial average pushing force of the same group, in N.

[0079] Table 2 Test results of pull-out force and retention rate of embedded copper block printed circuit boards after aging at 85℃ and 85%RH for 1000 hours.

[0080] As shown in Table 2, the push-out force of Example 12 after high temperature and high humidity aging was 2048 N, with a retention rate of 89.3%, both being the highest among all groups; the push-out force retention rate of Example 13 was 81.9%, lower than that of Example 12. In Example 12, the silica cage-like nodes formed by glycidyl POSS and the disiloxane bridging structure complement each other, which helps to improve the continuity of the interface network and restrict moisture migration along the interface.

[0081] Example 3 lacks an outer POSS reaction layer, Example 4 lacks an AMT coordination layer on the copper surface, and Example 5 lacks POSS silicon-oxygen cage nodes; none of these can simultaneously achieve copper surface bonding, epoxy co-curing, and interfacial moisture resistance. Examples 7-11 suffer from insufficient catalysis, lack of reactive groups in the POSS, one-time mixing of treatment components, reversed treatment order, or lack of epoxy silanes, resulting in insufficient interfacial crosslinking or discontinuous film formation. Example 2, through the combination of an AMT coordination layer, glycidyl POSS, and epoxy silanes, restricts moisture migration along the interface, thus exhibiting high hygrothermal stability.

[0082] Example 12 further introduces a disiloxane bridging structure into the interface system of Example 2, resulting in a higher moisture and heat retention rate than Example 2; Example 13 does not add glycidyl-based POSS, and its interface network lacks rigid silicon-oxygen cage nodes, thus reducing the moisture and heat retention rate accordingly.

[0083] Test Example 3 Fifteen independent samples were selected from the examples for temperature cycling tests. Ten of these samples were used for testing the copper block ejection force after temperature cycling, and the other five were used for interface slice observation after temperature cycling.

[0084] Each temperature cycle includes: (1) Lower the sample temperature to -40±2℃ and maintain it for 30 min; (2) Raise the sample temperature to 125±2℃ within 10 minutes; (3) Keep at 125±2℃ for 30 min; (4) Reduce the sample temperature to -40±2℃ within 10 minutes.

[0085] The temperature cycle was repeated 500 times. After the cycle was completed, the sample was placed in an environment with a temperature of 23±2℃ and a relative humidity of 50±5% for 2 hours, and then the pushing force of the copper block was measured according to the method of Test Example 1.

[0086] The thrust retention rate after temperature cycling is calculated using the following formula: R t =F t / F0×100% In the formula, R t F represents the force retention rate after temperature cycling. t F0 is the average push force after 500 temperature cycles, in N; F0 is the initial average push force of the same group, in N.

[0087] After the push-out force test, five pre-reserved temperature cycling samples from each group that had not undergone the push-out force test were taken and sliced ​​along the length and width of the oxygen-free copper block. The slices were then sequentially mounted, ground, and polished. Using an optical microscope with a measurement resolution of 0.01 mm at 200x magnification, the sidewalls, annular anchoring groove, adhesive guiding microgroove, and corners of the oxygen-free copper block were observed. The maximum length of continuous interface cracks in each sample was measured, and the average value of the five samples was taken. If no interface cracks were observed, they were recorded as less than 0.02 mm, according to the quantitative lower limit of the testing equipment.

[0088] Table 3 Test results of push-out force, retention rate and interface crack length of embedded copper block printed circuit board after 500 temperature cycles

[0089] As shown in Table 3, Example 12 exhibits the best overall performance with a push-out force of 2163 N after 500 temperature cycles, a retention rate of 94.3%, and an average maximum interfacial crack length of less than 0.02 mm. Example 13 shows a push-out force retention rate of 87.5% and an average maximum interfacial crack length of 0.05 ± 0.02 mm. In Example 12, the rigid POSS silicon-oxygen cage-like nodes, combined with the disiloxane bridging structure with conformational adjustment capabilities, effectively disperse interfacial thermal stress and suppress crack propagation.

[0090] Examples 3-5 lacked a POSS reactive layer, an AMT coordination layer, or glycidyl-based POSS, respectively, preventing the continuous transfer of interfacial load from the copper surface to the epoxy resin. Examples 7-11, due to insufficient catalysis, non-reactive POSS, improper treatment methods or sequences, and the lack of epoxy-based silanes, all exhibited varying degrees of reduced interfacial network integrity, resulting in long interfacial cracks after temperature cycling. Example 2 formed a composite interface consisting of an AMT coordination layer, POSS silica cage nodes, and an epoxy co-curing structure, which could disperse thermal cycling stress and inhibit crack propagation, thus demonstrating better temperature cycling reliability.

[0091] The preferred embodiments of the present invention have been described in detail above. It should be understood that those skilled in the art can make numerous modifications and variations based on the concept of the present invention without creative effort. Therefore, all technical solutions that can be obtained by those skilled in the art based on the concept of the present invention through logical analysis, reasoning, or limited experimentation on the basis of existing technology should be within the scope of protection defined by the claims.

Claims

1. A method for preparing an embedded copper block printed circuit board with high bonding reliability, characterized in that, Includes the following steps: Step 1: Select multiple double-sided copper-clad FR-4 core boards as inner layer core boards. Perform film lamination, exposure, development, etching, and film removal processes on the inner layer core boards in sequence to form the inner layer circuitry. After automatic optical inspection of the inner layer circuitry, perform browning treatment, water washing, and drying on the copper surface of the inner layer core boards. Prepare the first to fourth prepregs, the first outer copper foil, and the second outer copper foil. Step 2: Process openings corresponding to the installation positions of oxygen-free copper blocks on each double-sided copper-clad core board and on the first to fourth prepreg sheets respectively, and process copper block clearance windows on the first and second outer copper foils; after the double-sided copper-clad core boards are stacked, their openings together form a copper block positioning section, the openings on the first and fourth prepreg sheets form resin buffer sections on the upper and lower sides of the copper block positioning section, and the openings on the second and third prepreg sheets form resin flow channels. The copper block positioning section, resin buffer sections and resin flow channels together constitute a copper block receiving groove. Step 3: Process continuous closed annular anchoring grooves on the four sides of the oxygen-free copper block, and process adhesive guiding micro-grooves extending along the thickness direction of the oxygen-free copper block and communicating with the annular anchoring grooves on each side of the oxygen-free copper block; after degreasing, micro-etching and selective roughening of the oxygen-free copper block, immerse the oxygen-free copper block in the first treatment solution to form a coordination underlayer on the four sides of the oxygen-free copper block, the annular anchoring grooves and the adhesive guiding micro-grooves; then spray the second treatment solution onto the surface of the coordination underlayer. Step 4: Pre-stack the first outer copper foil, the first prepreg, the first double-sided copper core board, the second prepreg, the second double-sided copper core board, the third prepreg, the third double-sided copper core board, the fourth prepreg, and the second outer copper foil in that order, and then load the oxygen-free copper block into the copper block positioning section and position it. Step 5: Place the pre-stacked board obtained by pre-stacking in a vacuum press for staged vacuum pressing. First, the semi-cured sheet is gradually softened and the air inside the stack is discharged. Then, the softened epoxy resin is allowed to enter the gap between the oxygen-free copper block and the copper block positioning section through the resin buffer section, resin flow channel and adhesive guiding micro groove and fill the annular anchoring groove. Subsequently, the epoxy resin is cross-linked and cured to obtain the pressed board. Step 6: Remove excess adhesive from the surface and edges of the oxygen-free copper block, and perform double-sided grinding on the laminated plate to ensure that the exposed surface of the oxygen-free copper block is flat with the adjacent plate surface. Step 7: Drill holes in the laminate, remove adhesive with plasma, perform chemical copper plating and full-board electroplating, and fabricate the outer layer circuitry. Step 8: Form a solder resist layer on the board surface and form solder resist openings in the area of ​​the oxygen-free copper block that is used to contact the power devices. Perform surface treatment on the solder resist opening area to obtain the embedded copper block printed circuit board.

2. The method for preparing a high-reliability embedded copper block printed circuit board according to claim 1, characterized in that, In step 2, the openings on the first and fourth prepregs extend outward by 0.2-0.3 mm on one side relative to the copper block positioning section; the openings on the second and third prepregs extend outward by 0.08-0.12 mm on one side relative to the oxygen-free copper block; the center position deviation of the openings of adjacent double-sided copper-clad laminates does not exceed 0.05 mm, the verticality deviation of the groove wall of the copper block positioning section does not exceed 0.08 mm, and the cumulative height deviation of the overlapping area does not exceed 0.05 mm.

3. The method for preparing a high-reliability embedded copper block printed circuit board according to claim 1, characterized in that, In step 3, the width of the annular anchoring groove opening is smaller than the width of the groove bottom. The bottom width of the annular anchoring groove is 0.3-0.4 mm and the depth is 0.15-0.22 mm. Each sidewall of the oxygen-free copper block is provided with two adhesive guiding microgrooves. The width of the adhesive guiding microgrooves is 0.15-0.25 mm and the depth is 0.05-0.1 mm. The edges of the oxygen-free copper block are provided with a rounded structure with a rounding radius of 0.08-0.12 mm.

4. The method for preparing a high-reliability embedded copper block printed circuit board according to claim 1, characterized in that, In step 3, the four sides, annular anchoring groove, and adhesive guiding microgroove of the oxygen-free copper block are selectively roughened to achieve a surface roughness Ra of 1.8-2.5 μm. The first treatment solution includes 0.1-0.3 g / L of 3-amino-5-mercapto-1,2,4-triazole, 50-100 mL / L of isopropanol, and the remainder is water. The pH of the first treatment solution is adjusted to 8-8.8 using ammonia. The selectively roughened oxygen-free copper block is immersed in the first treatment solution for 20-40 min, rinsed with water, and dried at 60-70℃ for 10-15 min.

5. The method for preparing a high-reliability embedded copper block printed circuit board according to claim 1, characterized in that, In step 3, the second treatment solution comprises 0.2-0.6 wt% of an organosilicon modifier, 0.2-0.5 wt% of γ-glycidyl etheroxypropyltrimethoxysilane, 0.005-0.02 wt% of 2-ethyl-4-methylimidazole, 2-4 wt% of water, and the balance being a mixed solvent composed of ethanol and ethyl acetate in a mass ratio of 3:1-5:

1.

6. The method for preparing a high-reliability embedded copper block printed circuit board according to claim 1, characterized in that, The second treatment liquid is sprayed onto the surface of the coordination substrate, pre-baked at 70-80℃ for 10-15 min, and then reacted at 110-125℃ for 20-30 min.

7. The method for preparing a high-reliability embedded copper block printed circuit board according to claim 1, characterized in that, In step 1, the first and fourth prepregs are high-flowability, high-glass transition temperature epoxy resin prepregs with a resin content of 56-60%, and the second and third prepregs are medium-flowability, high-glass transition temperature epoxy resin prepregs with a resin content of 46-50%. In step 4, a 0.04-0.08mm single-sided gap is formed between the four sidewalls of the oxygen-free copper block and the positioning section of the copper block. A compressible resin compensation sheet is provided on the lower surface of the oxygen-free copper block, and the upper and lower surfaces of the oxygen-free copper block are respectively covered with polyimide release films.

8. The method for preparing a high-reliability embedded copper block printed circuit board according to claim 1, characterized in that, Step 5, the staged vacuum pressing, includes: In the first stage, under a vacuum degree not exceeding 5 kPa, the pre-stacked plates are heated to 85-95℃, a pressure of 0.2-0.4 MPa is applied and maintained for 15-25 minutes. In the second stage, the pre-stacked plates are heated to 130-140℃, and the pressure is increased to 0.7-0.9MPa and maintained for 10-20 minutes. In the third stage, the pre-stacked plates are heated to 180-190℃, the pressure is increased to 1.3-1.7MPa and maintained for 80-100min; after the pressure holding is completed, the plates are cooled to 95-105℃ while maintaining the pressure, and then cooled to 40-50℃ after the pressure is released.

9. The method for preparing a high-reliability embedded copper block printed circuit board according to claim 1, characterized in that, In step 6, the excess adhesive on the surface and edges of the oxygen-free copper block is removed by controlled-depth milling. Then, the laminated plate is double-sided ground with 600-mesh and 1000-mesh ceramic brush rollers to ensure that the height difference between the exposed surface of the oxygen-free copper block and the adjacent plate surface is within ±0.03mm. In step 7, connecting holes extending to the oxygen-free copper block are machined at the locations where electrical connection with the oxygen-free copper block is required. The copper layer on the hole wall of the connecting hole is electrically connected to the oxygen-free copper block through plasma adhesive removal, chemical copper plating, and electroplating. In step 8, the solder mask opening area is treated with immersion nickel gold.

10. A high-reliability embedded copper block printed circuit board, characterized in that, It is prepared by the preparation method described in any one of claims 1-9.

Citation Information

Patent Citations

  • Embedded-copper-block printed circuit board and manufacture method thereof

    CN108419361A

  • Method for embedding copper block of double-sided circuit board

    CN110996520A

  • Manufacturing method of copper block-embedded PCB

    CN113891584A